RANCANG BANGUN FETAL DOPPLER NIRKABEL BERBASIS ESP32 DAN NRF24L01 UNTUK TRANSMISI AUDIO DAN NILAI FHR - Aditya Lutfi Nurfathoni (Jurnal Ilmiah Poli Rekayasa, 2025)
Fetal doppler is an important device for monitoring fetal heart rate (FHR) as an early indicator of pregnancy condition. However, conventional fetal doppler devices still rely on cables between the probe and the main unit, thus limiting movement, reducing the comfort of pregnant women, and increasing the risk of cable damage. This study aims to design and build a wireless fetal doppler module based on ESP32 and nRF24L01 on the Taff Omicron JLS-T501 device for wireless transmission of doppler audio signals and FHR values. The developed system consists of a transmitter module on the probe side that performs acquisition, conditioning, and digitization of audio signals, then transmits data via nRF24L01, as well as an ESP32-based receiver module that reconstructs doppler audio and displays FHR values via an IoT interface. Testing was conducted using a fetal heart rate simulator at several BPM categories and distance variations (20–200 cm) to evaluate FHR accuracy, audio quality, and communication reliability. The results showed that the FHR reading error against the reference value was in the range of 1-2%, with audio quality remaining clearly audible up to a distance of 200 cm without interruption. This indicates that the integration of a wireless module on the JLS-T501 fetal doppler can improve flexibility and ergonomics of use without sacrificing measurement accuracy.